Subsequent Effect of Dietary Lysine Regimens Fed in the Starter Phase on the Growth Performance, Carcass Traits and Meat Chemical Composition of Aseel Chicken in the Grower Phase - Hussain,M (2018)
ABSTRACT This study was designed to examine carryover effect of dietary lysine (Lys) levels fed during the starter phase on the growth performance of three varieties of Aseel chickens. A total of 378 birds (126 from each variety) derived from a previous experiment, in which birds were distributed according a randomized block design in a 3×3 factorial arrangement, were evaluated from 7-18 weeks of age. Treatments consisted of three varieties of Aseel chicken [(Mianwali (MW), Peshawari (PW) and Lakha (LK)] fed three dietary Lys regimes (high, medium and low) during the starter phase (0-6 weeks). In the present experiment, the performance parameters, carcass traits, and meat chemical composition six replicates of seven birds per treatment were evaluated. The MW variety exhibited higher weight gain and better feed to gain ratio (p<0.05). Previous medium dietary Lys regimen improved weight gain, feed to gain ratio, final weight gain (p≤0.05). Birds previously fed medium dietary Lys showed higher thigh dry matter content (p<0.05), and those previously fed low Lys significantly higher thigh crude protein (CP) content (p<0.05). The highest breast muscle CP % were observed birds previously fed the high Lys regime (p<0.05), those of the MW variety (p<0.05). Higher slaughter weight and carcass weight and yield were obtained in the birds previously fed to medium dietary Lys level (p<0.05), and the MW variety showed overall better carcass traits (p<0.05). It is concluded that medium Lys levels in the starter feed promote subsequent better growth performance and that the MW variety has better carcass traits, it may be used as for rural chicken meat production.